(untitled) (The Research of Medical Science Review, 2025)
Background: Deep vein thrombosis (DVT) in the lower limbs is a frequent and dangerous disorder that can result in pulmonary embolism. Doppler ultrasound is the suitable diagnostic method since it is non-invasive and sensitive. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines but does not include a meta-analysis are adhered to in this systematic review. The purpose of the study is to use Doppler ultrasound and related risk factors to ascertain the prevalence of lower limb deep vein thrombosis (DVT). The databases of PubMed, EMBASE, Scopus, and Cochrane were thoroughly searched. Results: Studies conducted worldwide on the prevalence and risk factors of deep vein thrombosis (DVT) are examined in this systematic review. Involvement of the left leg was most common, with prevalence rates ranging from 3.1% to 57%. Cancer, diabetes, surgery, and previous DVT were major risk factors. These results highlight the significance of identifying populations at risk in order to improve management and preventative tactics. Conclusion: Although the occurrence of DVT varies greatly, common risk factors include diabetes, malignancy, immobilization, and surgery. It is more common in women and elderly persons, and it usually affects the left leg. For high-risk groups, early identification is essential.